ANALYSIS OF TEAM WORK ABILITY OF 11TH GRADE STUDENT OF COMPUTER AND INFORMATICS ENGINEERING STUDY PROGRAM AT VOCATIONAL SCHOOL IN KEBUMEN DISTRICT - Endang Wahyuningsih; Khofiyati Khofiyati (Universitas Sebelas Maret, 2018)
In encountering globalization era, Indonesia is required to prepare high-skilled and professional human resource. Unfortunately, in these days Indonesia still face the lack of high-skilled and professional human resource. One of the solutions is human resource quality improvement through vocational school (SMK). Team work is one of important skill needed in order to be professional worker. This study aims to find out the level of team work of 11th grade students of Computer and informatics engineering (TKI) study program vocational school in Kebumen district.This study is a descriptive qualitative research. The subject of this research consists of 99 students.The instrument used in this research was team work questionnaires.The result of data analysis shows that the percentage of students who have team work ability categorized as “Very Good” was 14.14%, “Good” was 63.64%, and “Good enough” was 22,22%. It can be concluded that students’ team work ability was categorized “Good”.